ANALISIS HUKUM PERAN PEMERINTAH DAERAH DALAM PENYEDIAAN LAYANAN KESEHATAN REPRODUKSI DI KOTA MAKASSAR - Muh. Tahir; A. Melantik Rompegading; Ali Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The 1945 Constitution guarantees the right to health, including the reproductive health of adolescents who are vulnerable to the TRIAD KRR. The central and regional governments are obliged to provide health services through decentralization. However, implementation faces challenges of coordination, funding, and regional capacity, so legal analysis is needed to assess the effectiveness of reproductive health policies. To examine and analyze the role of local governments in the provision of reproductive health services in Indonesia and To examine and analyze the barriers faced by local governments in the provision of reproductive health services. This study is an Empirical legal research using a Legislative Approach and a Conceptual Approach. The role of local governments in the provision of reproductive health services has been regulated in Law No. 17 of 2023 and Government Regulation No. 28 of 2024, with the obligation to provide promotive, preventive, curative, and rehabilitative services. Although various programs have been implemented, implementation is still constrained by limited human resources, infrastructure, and coordination.